Edaphic influences on the nutrient concentrations and antioxidant activity of different tea clones (Camellia sinensis (O.) Kuntze) grown at the lowland tea plantation, Bukit Cheeding, Selangor, Malaysia - S. S., Amirah; M., Khairil; W. E, Murdiono; Halmi, M. I. E.; R., N. Amalina; Yong, J. W. H.; Burslem, D. F. R. P. (Malaysian Society of Soil Science, 2023)
Tea (Camelia sinensis) is one of the most consumed beverages in the world. Research on the nutritional characteristics of tea, particularly lowland tea plantations, is limited in Malaysia. Thus, we aimed to investigate the nutritional characteristics (N, P, K, Ca, Mg, Al, Fe) and antioxidant activity of seven clonal teas (663, 2026, 2024, AT53, TV9, 1294, and 1428) planted at a tropical lowland tea plantation, Bukit Cheeding, Selangor, and their association with the soil edaphic factor. All foliar nutrient concentrations except for Ca and antioxidant activities varied significantly (p<0.05) among tea clones. Clone AT53 had the highest foliar K (1.84 ± 0.7 mg g-1 ), Mg (0.80 ± 0.3 mg g-1 ), Fe (12.97 ± 1.4 mg g-1 ), and Al (16.61± 1.4 mg g-1 ). Clone 663 had the highest P (13.76 ± 1.06 mg g-1 ), and clone 2026 had the highest N (4.39 ± 0.2%). Clone 1248 had the highest antioxidant activity at 50.66 ± 3.2 µg mL-1 . Tea foliar N and P concentrations were significantly associated with the N and P of the soil. Besides, several soil nutrients were significantly intercorrelated with foliar nutrient concentrations. Results from this study may benefit growers in selecting better quality clones and managing lowland tea plantation at Bukit Cheeding, Selangor, Malaysia. Good farm management may improve the productivity and sustainability of tea plantations.